Assessment of lifetime attributable risk (LAR) of cancer incidence from whole-body 18F-FDG PET/CT examinations using established polynomial fittings - Murat, H.; Kechik, M.M.A.; Chew, M.T.; Kamal, I.; Said, M.A.; Karim, M.K.A. (EDP Sciences, 2025)
The advent of PET/CT examinations has revolutionized cancer treatment, offering greater precision in diagnosis. Nonetheless, the ionizing radiation exposure during the examination could cause radiation cancer risk. Hence, this study aimed to evaluate the radiation dose and radiation-induced risk associated of whole-body PET/CT examinations that includes the 18F-FDG radionuclides. For this retrospective study, 40 participants were studied, with 20 men and 20 women. The average age and weight of the participants were 53.77 ± 15.78 years and 66.59 ± 16.94 kg respectively, and they were administered 424.64 ± 121.19 MBq of 18F-FDG before the PET/CT commenced. The IDAC-Dose 2.1 program was employed to calculate the absorbed dose and effective dose in organs such as the bladder, brain, lung, kidneys, colon, red bone marrow (RBM), stomach, liver, and thyroid. In this study, polynomial regression was used to fit the Lifetime Attributable Risk (LAR) values derived from the BEIR VII phase II report. The effective dose from the 18F-FDG PET/CT examination was 20.1 ± 7.9 mSv, with a ratio of E to the administered activity of 1.612 × 10-2 mSv/MBq, in accordance with ICRP standards. The related risk of cancer in the second part of the work did not include CT component. The estimated average cancer incidence from the PET alone was 7 and 8 cases per 100,000 persons exposed to 0.1Gy for men and women respectively, with PET-related effective doses ranging between 3.2 mSv to 27.3 mSv. In summary, the risk of cancer associated with current whole-body 18F-FDG PET/CT examinations is low, but it is essential to mitigate radiation exposure during these examinations and utilize suitable techniques to prevent stochastic effects from low-dose radiation exposure. © H. Murat et al.